Hungarian Monitoring, 13 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Unacceptable Iraqi proposals over the course of the Gulf conflict - Cairo to send more soldiers - Conflicts in Solidarity - Berlin Wall is 29 years old - Gorbachev rehabilitated victims of Stalinism Domestic Affairs: - József Antall and the Slovak premier's accusations - Disputed Jeszenszky statement on Romania - World Humanist Congress in Budapest - Gyula Thürmer on the new 'B-list' of politically-motivated dismissals Economy: - Loan to develop telephone network - World Bank plan to privatize 33 Hungarian companies by bringing in foreign capital - Economic consequences of the Middle Eastern conflict - Personnel changes in economic life - Unemployment Külpolitika: - Elfogadhatatlan iraki javaslatok az öbölbeli konfliktus során - Kairó további katonákat küld - Konfliktusok a Szolidaritásban - 29 éves a berlini fal - Gorbacsov rehabilitálta a sztálinizmus áldozatait Belpolitika: - Antall József és a szlovák miniszterelnök vádjai - Vitatott Jeszenszky-nyilatkozat Romániáról - Humanista Világkongresszus Budapesten - Thürmer Gyula az új B-listázásról Gazdaság: - Hitel a telefonhálózat fejlesztésére - Világbank-terv 33 magyar vállalat külföldi tőke bevonásával történő privatizációjára - A közel-keleti konfliktus gazdasági következményei - Fejcserék a gazdasági életben - Hajléktalanság